Interval Type-2 Fuzzy Sliding Mode Resilient Control via Probability-Dependent Adaptive Event-Triggered Scheme - Yang, Yekai; Niu, Yugang; Lam, James (IEEE transactions on systems, man, and cybernetics. Systems, 2023)
This article focuses on the event-triggered sliding mode control for interval type-2 (IT2) fuzzy systems subject to the randomly occurring denial-of-service (DoS) attacks. Under the resource-limited and unreliable network, a probability-dependent adaptive event-triggered scheme (AETS) is proposed, whose triggering parameter can be adaptively adjusted in accordance with the convergence trend of the system state and the attack probability. By constructing a sliding function with one-step-memorized state information, a fuzzy sliding mode resilient controller is designed, whose membership functions (MFs) dependent on the compromised triggered state do not require the same fuzzy rules as the fuzzy system. Furthermore, by employing the global bounds of mismatched MFs, the co-design conditions for the AETS and the fuzzy controller are derived for attaining both the reachability and the stability. Finally, a simulation example and the comparison results are provided.